Long noncoding RNAs: Emerging players regulating innate immune memory in the red flour beetle. (February 2022) - Abd El Halim, Hesham M.; Ali, Ali
Abstract: A variety of strategies have been evolved to eradicate invading microbes. Phagocytes have developed in vertebrates and invertebrates to confer a non-specific immune response to pathogens. Besides, vertebrates have evolved lymphocytes to develop memory cells that can quickly respond upon the next exposure to the same pathogen. Although lymphocytes are absent in invertebrates, historical evidence, dating back to the 1920s, indicated the presence of immune memory in invertebrates. However, the concept of long-lasting non-specific defense predominated until recent evidence has been introduced in the first decade of the 21st century. Although more evidence has been introduced later, the molecular mechanism underlying the innate immune memory is largely undefined in invertebrates. Long noncoding RNAs (lncRNAs) have demonstrated a role in regulating various biological processes, including immune response. In this review, we will explore the potential role of lncRNAs in developing innate immune memory in the red flour beetle ( Tribolium castaneum ). Highlights: Immune memory response was demonstrated by a shift in the lncRNA expression. Phagocytosis has been demonstrated as an important effector in the priming response. Priming lncRNAs exhibited a role in histone methylation to develop innate immune memory.